Prevalence Rates of Toxoplasmosis among Pregnant Women in Sebha, Libya - bernawi, Abdulkadir; Ramadan, Kareman; khan, Abdulhafeez (Journal of Pure & Applied Sciences, 2018)
The seroprevalence of toxoplasmosis in 267 randomized pregnant women attending different clinics in Sebha, Libya (during the period of December 2012 to October 2013), was determined by Enzyme-Linked Immunosorbent Assay (ELISA). Anti-Toxoplasma gondii lgG and lgM were found in 69 (25.89%) and 42 (15.73%) respectively. The overall positivity of antibodies was 25.89% (69/267) in different localities of Sebha city. None of the total serum sample showed positive results for Toxoplasma IgM antibodies and was found negative for Toxoplasma lgG antibodies. Specific IgM antibody positivity is indicative of possible of acute toxoplasmosis among pregnant women. (69 0f 267) seropositive for anti-T.gondii lgG antibodies 25.89% pregnant women, suggesting that were chronically infected, while 15.73% (42 of 267) seropositive for T.gondii lgM antibodies acquired infection of T.gondii during pregnancy. The difference between presence of lgG and lgM antibodies was significant ( 2= 5.447, P= 0.020) .No significant difference ( 2= 1.22 , P = 0.748 ) was found in the prevalence rates of anti-T.gondii lgM antibodies among different age groups of pregnant women. Significant association ( 2= 6.465,P=0.011) was found between seroprevalence of anti-T.gondii lgM and the presence of cats at home of patients. Consumption of undercooked meat was also found significantly associated with the presence of anti-T.gondii lgM among pregnant women      ( 2= 5.338, P=0.021). No significant correlation was found between seropositivity of anti- T.gondii antibodies and abortion history of patients( 2= 3.037, P=0.081). Prevalence rate of anti-T.gondii lgM among symptomatic and asymptomatic pregnant women was not statistically significant( 2= 0.164, P=1.93).ELISA appeared to be suitable for routine serology of both chronic and acute toxoplasmosis among pregnant women.